Studi Perbandingan Pembagian Warisan Menurut Sistem Hukum Waris Adat Kaum Dengan Sistem Hukum Waris Islam Di Kecamatan Kota Mukomuko Kabupaten Mukomuko - Muslih, Akhmad; Sauni, Herawan; Sofyan, Tito (Jurnal Ilmiah Kutei, 2023)
This research aims to find knowledge about comparing inheritance distribution according to the traditional Kaum inheritance law system with the Islamic inheritance law system in Kota Mukomuko District, Mukomuko Regency. The method used is an empirical research method with comparative and qualitative approaches. The research results are as follows: First, in traditional inheritance, girls receive more inheritance assets than boys, except for high inheritance assets and sukang/soaring assets, because the people of Mukomuko City District adhere to the matrilineal principle in determining inheritance rights, low inheritance assets, livelihood assets, following matrilineal principles. Second, the division of inheritance in Islamic law has been stipulated in the Al-Qur'an in detail using mathematical calculations, as in the Al-Qur'an Surah An-Nisa verses (7), (11), (12), (33), and (176). Every heir from Dzawil Furudh, Ashabah, or Dzawil Arham gets a clear, systematic and unmixed share. In the principle of distribution of Islamic inheritance, sons receive a larger share than daughters; in principle, men are responsible for their children and wives; women have personal rights to their property, such as women's property from the results of their work, women's property is her property, apart from her husband's property. Third, the Kaum customary law system "privileges female heirs" with matrilineal principles, and the Islamic inheritance law system "privileges sons." there is an opinion that Islamic law follows patrilineal principles. The traditional Kaum inheritance law system is individual-collective. In contrast, the Islamic Law inheritance system is individual-bilateral, prioritizing balanced justice in life, placing the best and fairest principles in transferring a person's ownership after death to his heirs; all heirs get rights, without distinguishing between men and women, big or small.